2017
DOI: 10.1097/shk.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Fc Gamma Receptor IIB Deficient Mice

Abstract: Hyper-elevated immune response of FcGRIIb-/- mice, a lupus model with an inhibitory-signaling defect, can become exhausted (less subsequent immune-response than the first response) with sequential lipopolysaccharide (LPS) stimulation. Endotoxin tolerance-related modifications of inflammatory response were investigated in FcGRIIb-/- mice in both an in vivo sepsis model and in vitro using cultured macrophages. Serum cytokine concentrations, after the second LPS injection (at 5-fold higher levels than the first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 34 publications
8
65
0
Order By: Relevance
“…B cells express only the inhibitory receptor FcγRIIb. It has been reported that FcγRIIB-deficient mice display an increased frequency of autoreactive B cells and lupus-like manifestations (25,26). Although monocyte/macrophage abnormalities play a pivotal role in the pathogenesis of SLE, the role of macrophages in spleen inflammation and splenomegaly is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…B cells express only the inhibitory receptor FcγRIIb. It has been reported that FcγRIIB-deficient mice display an increased frequency of autoreactive B cells and lupus-like manifestations (25,26). Although monocyte/macrophage abnormalities play a pivotal role in the pathogenesis of SLE, the role of macrophages in spleen inflammation and splenomegaly is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the overwhelming response to endotoxin (LPS) followed by the prominent immune exhaustion in FcGRIIb−/− mice [10]. Similarly, patients with lupus are susceptible to infection and this susceptibility towards infection is increased in patients with immune exhaustion [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lupus characteristics as determined by serum creatinine, proteinuria, and anti-dsDNA in FcγRIIb-/- mice after 24-week-old is previously described ( Ondee et al, 2017 ; Surawut et al, 2017 ). Hence, HP administration in 24-week-old mice represents HP infection in patients with symptomatic lupus.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages were derived from the bone marrow (BM) ( Ondee et al, 2017 ) and phagocytosis assay was performed following an established protocol ( Chmiela et al, 1997 ; Miliukene et al, 2007 ). In short, 1 × 10 9 cell/ml heat-killed HP (60°C for 30 min) was incubated with 100 μg/ml fluorescein isothiocyanate (FITC) (Sigma, United States) in PBS at 35°C for 30 min for FITC-labeling.…”
Section: Methodsmentioning
confidence: 99%